2000
DOI: 10.1128/aac.44.5.1247-1254.2000
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of Glycopeptides in the Mouse Peritonitis Model ofStreptococcus pneumoniaeorStaphylococcus aureusInfection

Abstract: The emergence of resistance to various antibiotics in pneumococci leaves the glycopeptides as the only antibiotics against which pneumococci have no resistance mechanism. This situation has led to a renewed interest in the use of glycopeptides. It has not yet been possible to conclude which one or more of the pharmacokinetic or pharmacodynamic (PK/PD) parameters are the most important and best predictors for the effects of treatment with glycopeptides in animal models or in humans. We used the mouse peritoniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(49 citation statements)
references
References 24 publications
(47 reference statements)
1
47
0
Order By: Relevance
“…T >MIC was thus initially pneumoniae as infective organisms [24]. The data showed that C max-free was of major importance in the one-and two-dose trials, but this parameter alone could not explain the effects achieved in the multidose trials.…”
Section: Glycopeptidesmentioning
confidence: 78%
“…T >MIC was thus initially pneumoniae as infective organisms [24]. The data showed that C max-free was of major importance in the one-and two-dose trials, but this parameter alone could not explain the effects achieved in the multidose trials.…”
Section: Glycopeptidesmentioning
confidence: 78%
“…However, experimental models in neutropenic mice have shown some concentration-dependent activity [maximum drug concentration/minimum inhibitory concentration ratio (C max /MIC)], with advantages also evident when the area under the concentration-time curve (AUC) to MIC ratio (AUC/MIC) is maximised [2]. Therefore, the question remains whether intermittent dosing or continuous infusion is preferred.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters calculated were: peak drug concentration in serum (C max ), elimination half-life (T 1/2 ), area under the concentration-time curve (AUC), inhibitory quotient (IQ; IQ ϭ C max /MIC), and time above the MIC of the drug concentration in serum (T Ͼ MIC). Based on previous studies, 6,15,16 human data, 7,21,30 and …”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Different time points were tested to study the evolution of the infection and appropriate time points were set for starting therapy. Groups of mice were killed at 4,8,16, and 24 hr postinoculation to obtain blood and peritoneal fluid (PF) samples as described below. Bacterial counts and bacteremia were determined for each mouse and time point.…”
Section: Mouse Peritonitis Modelmentioning
confidence: 99%
See 1 more Smart Citation